2016
DOI: 10.1016/j.wasman.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Production of activated carbons from waste tyres for low temperature NOx control

Abstract: Waste tyres were pyrolysed in a bench scale reactor and the product chars were chemically activated with alkali chemical agents, KOH, K2CO3, NaOH and Na2CO3 to produce waste tyre derived activated carbons. The activated carbon products were then examined in terms of their ability to adsorb NOx (NO) at low temperature (25 °C) from a simulated industrial process flue gas. This study investigates the influence of surface area and porosity of the carbons produced with the different alkali chemical activating agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…Therefore, although PF is a non-graphitizable material, ACs synthesized from this precursor presents outstanding physicochemical properties, with equal or even better results than most of the graphitizable precursors offering an interesting destination for waste PF [4,24,39,40].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although PF is a non-graphitizable material, ACs synthesized from this precursor presents outstanding physicochemical properties, with equal or even better results than most of the graphitizable precursors offering an interesting destination for waste PF [4,24,39,40].…”
Section: Tablementioning
confidence: 99%
“…Activated carbons are commonly used products that have been produced from a large number of different precursors, which may be mineral, biological or synthetic [1][2][3]. Increasing concern about sustainability in our society is encouraging the production of re-usable materials obtained not from natural resources but from waste [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Its production combines carbonization of a raw carbon precursor at temperatures below 800°C in an inert atmosphere and chemical or physical activation of an as-obtained semi-product. [62][63][64] The popular raw materials include coal with a various degree of metamorphosis (both low and high degrees of coalification, 65 brown coal, 66 peat, 67 charcoal, 68 seeds of fruits, nut shells and other lignocellulose materials [69][70][71][72][73][74][75][76][77] ), as well as industrial waste, 78 waste from the agri-food industry, [79][80][81][82][83] sewage residues, [84][85][86][87][88] waste tyres [89][90][91] and plastic waste. [92][93][94] Pyrolysis results in elimination of oxygen, hydrogen and nitrogen atoms.…”
Section: Active Carbons and Carbonized Materialsmentioning
confidence: 99%
“…The polarization of coconut shell activated carbon is relatively very low, and effectively forms covalent bonds with NOx, which has dipole moments in similar ranges to that in coconut shell activated carbon [9,13]. In addition, coconut shell activated carbon can physically adsorb NOx because its pore size is similar to movement range of the NOx gas molecules [14]. Park et al [15] reported that the NOx removal rate of coconut shell activated carbon was improved by 40% after plating the surface of the coconut shell activated carbon with Cu.…”
Section: Introductionmentioning
confidence: 99%